2017
DOI: 10.1111/jfs.12353
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of curcumin nanoparticles against Listeria monocytogenes is mediated by surface charge

Abstract: Curcumin, a hydrophobic phenolic compound isolated from tumeric (Curcuma longa), has gained a great attention due to its health benefits and antimicrobial effects. In this study, curcumin nanoparticles (CNPs) were formulated via acusto‐plastic deformation technique, with three differently surface‐charged surfactants‐sodium dodecylsulfate, Tween 20 and cetrimonium bromide (CTAB). The fabricated CNPs were evaluated for their antimicrobial activity against Listeria monocytogenes, one of the most severe foodborne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
(24 reference statements)
2
14
0
Order By: Relevance
“…No et al described a relationship between surface charge and antimicrobial activity of nanocurcumin. Experimental data confirmed that positively charged curcumin nanoparticles showed better antimicrobial activity against Listeria monocytogenes (No et al, 2017).…”
Section: Comparative Characteristics and Efficacy Of Nanocurcumin Andmentioning
confidence: 60%
“…No et al described a relationship between surface charge and antimicrobial activity of nanocurcumin. Experimental data confirmed that positively charged curcumin nanoparticles showed better antimicrobial activity against Listeria monocytogenes (No et al, 2017).…”
Section: Comparative Characteristics and Efficacy Of Nanocurcumin Andmentioning
confidence: 60%
“… 191 Curcumin nanoformulations have been shown to have minimum inhibitory concentration of ∼1 mg/mL while the crude one had 350 mg/mL. 192 It reflects the superior anti-pathogenic activity of curcumin when encapsulated in nanoparticles. The PEGylated lipid formulations of curcumin have been found to be 10-fold more effective for malaria than crude curcumin.…”
Section: Nanotheranostics Perspectivementioning
confidence: 99%
“…10b) [41,42]. Pandit et al also reported the improved antibacterial efficacy of micro/nanocurcumin over curcumin [45][46][47]. Similarly, micro/nanocurcumin exhibited improved antibacterial potential than curcumin against S. aureus at 200 μg/mL and 500 μg/mL concentration having 49% and 55% antibacterial activity (at sixth hour) with respect to control (Fig.…”
Section: Antibacterial Effect Of Micro/nanocurcuminmentioning
confidence: 82%
“…Gopal et al also demonstrated the improved antibacterial potential of nanocurcumin against S. aureus than macro-and microcurcumin [26]. Although several factors like size, solubility, stability, and method of synthesis determine antibacterial potential of nanocurcumin, literature survey suggests that the MBC of nanocurcumin against S. aureus ranges from 100 μg/mL, 250 μg/mL, to 608 μg/mL [45][46][47][48][49][50], the present study also exhibited that micro/nanocurcumin at 200 μg/mL and 500 μg/mL inhibited the S. aureus growth with almost 50% inhibitory potential compared to control (Fig. 10b).…”
Section: Antibacterial Effect Of Micro/nanocurcuminmentioning
confidence: 99%